Experimental and numerical analysis of refill friction stir spot welding of thin AA7075-T6 sheets - Janga, V.S.R. (MDPI, 2021)
The refill friction stir spot welding (refill FSSW) process is a solid-state joining process to produce welds without a keyhole in spot joint configuration. This study presents a thermo-mechanical model of refill FSSW, validated on experimental thermal cycles for thin aluminium sheets of AA7075-T6. The temperatures in the weld centre and outside the welding zone at selected points were recorded using K-type thermocouples for more accurate validation of the thermo-mechanical model. A thermo-mechanical three-dimensional refill FSSW model was built using DEFORM-3D. The temperature results from the refill FSSW numerical model are in good agreement with the experimental results. Three-dimensional material flow during plunging and refilling stages is analysed in detail and compared to experimental microstructure and hardness results. The simulation results obtained from the refill FSSW model correspond well with the experimental results. The developed 3D numerical model is able to predict the thermal cycles, material flow, strain, and strain rates which are key factors for the identification and characterization of zones as well for determining joint quality. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.